Requirements Engineering and Software Testing in Agile Methodologies: a Systematic Mapping - Coutinho, Jarbele C. S.; Andrade, Wilkerson L.; Machado, Patrícia D. L. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
The insertion of agile practices in software development has increased exponentially. Both industry and academic staff constantly face challenges related to requirements specification and testing in this context. In this study, we conducted a systematic mapping of the literature to investigate the practices, strategies, techniques, tools, and challenges met in the association of Requirements Engineering with Software Testing (REST) in the agile context. By searching seven major bibliographic databases, we identified 1.099 papers related to Agile REST. Based on the systematic mapping guidelines, we selected 14 of them for a more specific analysis. In general, the main findings include the fact that weekly meetings should be held to establish frequent communication with stakeholders. Also, most projects adopt use cases as conceptual models and perform use case detailing. Test cases are an important artifact with test case design as a Software Testing practice. For the automation of test cases, fit tables have been recommended as an artifact. Finally, proper project documentation constitutes a critical basis in Agile REST.